2020
DOI: 10.20885/jaai.vol24.iss1.art1
|View full text |Cite
|
Sign up to set email alerts
|

Does CSRD moderate the effect of financial performance on stock return? Evidence of Indonesian mining companies

Abstract: The purpose of this study is to examine the effect of financial performance on stock returns with corporate social responsibility disclosure as a moderating variable in mining companies listed on the Indonesia Stock Exchange (IDX) 2014-2016 period. This study used multiple linear regression to examine the corporate social responsibility disclosure in moderating the effect of financial performance on stock returns. The measurement of financial performance uses financial ratios, namely return on equity. The test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
1
9
0
4
Order By: Relevance
“…Quality companies with good financial performance will certainly have value that continues to grow in the eyes of investors, thereby increasing the company's stock price [4,10]. This result is in line with research by [20,38] which found that investor decisions are influenced positively and significantly by profitability.…”
Section: Ic-heds 2019supporting
confidence: 55%
See 2 more Smart Citations
“…Quality companies with good financial performance will certainly have value that continues to grow in the eyes of investors, thereby increasing the company's stock price [4,10]. This result is in line with research by [20,38] which found that investor decisions are influenced positively and significantly by profitability.…”
Section: Ic-heds 2019supporting
confidence: 55%
“…Then there is research that found that investor decisions on investment are also influenced by capital structure [2,3,42]. However, in the research of [16] as well as [20] no effect of capital structure was found on investor investment decision.…”
Section: Ic-heds 2019mentioning
confidence: 99%
See 1 more Smart Citation
“…Kinerja keuangan perusahaan, khususnya laba yang dilaporkan, bukanlah variabel yang berdiri sendiri untuk memengaruhi keputusan investor, karena dari sejumlah penelitian ditunjukkan bukti bahwa respon investor pada kinerja keuangan menjadi makin besar ketika perusahaan memiliki kepedulian tinggi pada masalah sosial dan masalah lingkungan hidup; sebaliknya, respon investor melemah apabila perusahaan menunjukkan kepedulian rendah pada masalah sosial dan masalah lingkungan hidup (Riduwan dan Andayani, 2019;Hapsoro dan Husain, 2019;Kim et al, 2018). Hasilhasil penelitian tersebut dapat digunakan sebagai penjelas bahwa investor memiliki kesadaran dan keyakinan bahwa kinerja keuangan, yang akan mewujud sebagai kembalian investasi (return), bukanlah tujuan sesaat, tetapi harus berkelanjutan dalam jangka panjang.…”
Section: Pendahuluanunclassified
“…The share price is the price that occurs at some point possible due to the supply and demand among the buyer and the seller of the stock. Certain circumstances and situations that can change stocks include the company's policy on expansion including micro and macroeconomic conditions, such as opening agencies, branches both at home and abroad; a sudden change in the position of manager or commissioner of the company involved in criminal acts and cases (Hapsoro & Husain, 2019;Haris et al, 2019;Le et al, 2020;Sharma et al, 2020).…”
Section: Stock Pricementioning
confidence: 99%